2019
DOI: 10.3389/fphys.2019.00930
|View full text |Cite
|
Sign up to set email alerts
|

Novel GLP-1 Analog Supaglutide Stimulates Insulin Secretion in Mouse and Human Islet Beta-Cells and Improves Glucose Homeostasis in Diabetic Mice

Abstract: Glucagon-like peptide-1 (GLP-1), an incretin hormone plays an important role in regulating glucose homeostasis. The therapeutic use of native GLP-1 is inadequate due to its short in vivo half-life. We recently developed a novel GLP-1 mimetics supaglutide, and demonstrated that this formulation retained native GLP-1 biological activities and possessed long-lasting GLP-1 actions. In this study, we further examined its abilities in regulating blood glucose in diabetic mice. We found that su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…This is consistent with other's observations that in diet-induced obese mice and non-human primates, GLP-1 based therapy significantly reduced blood glucose, and reduced body weight mainly due to the increased lipid and carbohydrate oxidation and energy consumption (Elvert et al 2018). Supaglutide treatment improved glucose tolerance associated with improved β-cell function, exemplified by enhanced insulin secretion, particularly in the first phase during IVGTT in diabetic monkeys, consistent with our recent data showing that long-term treatment with supaglutide stimulates insulin secretion and enlarges β-cell mass in diabetic db/db mice (Ren et al 2019).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is consistent with other's observations that in diet-induced obese mice and non-human primates, GLP-1 based therapy significantly reduced blood glucose, and reduced body weight mainly due to the increased lipid and carbohydrate oxidation and energy consumption (Elvert et al 2018). Supaglutide treatment improved glucose tolerance associated with improved β-cell function, exemplified by enhanced insulin secretion, particularly in the first phase during IVGTT in diabetic monkeys, consistent with our recent data showing that long-term treatment with supaglutide stimulates insulin secretion and enlarges β-cell mass in diabetic db/db mice (Ren et al 2019).…”
Section: Discussionsupporting
confidence: 85%
“…During the intervention period of 4 weeks, although HbA1c was not obviously changed, the plasma FRA, a validated-biomarker that reflects the average levels of glucose control over the past 2-3 weeks (Ren et al 2019, Calderon et al 2020, was significantly decreased, in a dose-dependent fashion. The metabolic cycle of erythrocytes in rhesus monkeys is about 90 days (Pasini et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…In accordance with these findings, dual GLP-1 and GCG receptor agonist SAR425899 was recently shown to improve β-cell function 37 . In addition, it has previously been shown that GLP-1 receptor agonist supaglutide increases β-cell mass in severely diabetic mice 32 .…”
Section: Discussionmentioning
confidence: 96%
“…Despite being great weight loss candidates, GLP-1 and dual GLP-1 and GCG receptor agonists also improve overall glucose homeostasis in diabetic subjects [31][32][33] . Therefore, we assessed the effects of OXM-104, cotadutide, and semaglutide on glucose control in severely diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of this treatment, there was an enlargement in the mass of the islets, a promotion of β-cell proliferation, and enhancements in glucose tolerance and insulin secretion. 21 …”
Section: The Intestine and The Isletsmentioning
confidence: 99%